Penerapan Pembelajaran Online Berbasis Google Meet Untuk Meningkatkan Hasil Belajar Kimia Pada Siswa Kelas XI IPA 4 di SMA Negeri 1 Sumberpucung - Yayuk Wijiutami (CV. Gerasi Insan Nusantara, 2021)
Teacher involvement is very important to make learning fun. In the current education situation, not everything is smooth because Indonesia is one of the countries affected by the COVID-19 pandemic. School closures are an effort to prevent the spread of the COVID-19 virus. This causes many students to have difficulty in learning chemistry because they cannot meet face to face. The research method in this research is classroom action research (CAR). This research was carried out in class XI IPA 4 at SMA Negeri 1 Sumberpucung by applying online learning based on google meet. The result of this research is that in the first cycle students who experience complete learning are 66.66% and in the second cycle 91.66%. So that through google meet-based online learning can improve chemistry learning outcomes.